The Extent to Which Quality Standards and Labor Market Requirements Are Met in the Curricula of the Faculties of Economics and Arts at the University of Benghazi (Journal of human and social sciences, 2022)
The research aimed to determine the degree of availability of quality standards and the labour market requirements in the curriculum of the Faculties of Economics and Arts at University of Benghazi, as they are considered the largest faculties in terms of the number of students and teaching staff members. This research adopted the questionnaire as a means to collect the data needed in order to test the research hypothesis. The most important result revealed from the analytical statistics of data that the degree of availability of quality standards and labour market requirements in the curriculum of the Faculties of Economics and Arts at University of Benghazi were very low. In addition, the research found that there are differences between the average responses of the two research samples in terms of determining the degree of this decline. Based on the research findings, two recommendations can be made in this regard. First: the Ministry of Education must establish a higher council of curriculum, concerned with the development and follow-up the quality standards in educational curriculum. Second: relationships must be built between Benghazi University faculties and the economic units so that the university could contribute for the overall development of society.
Keywords: Quality standards; Requirements of the labour market; Curriculum of the Faculties of Economics and Arts at University of Benghazi